2019
DOI: 10.1097/aud.0000000000000697
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Listening Effort Are Multidimensional

Abstract: Objectives: Listening effort can be defined as the cognitive resources required to perform a listening task. The literature on listening effort is as confusing as it is voluminous: measures of listening effort rarely correlate with each other and sometimes result in contradictory findings. Here, we directly compared simultaneously recorded multimodal measures of listening effort. After establishing the reliability of the measures, we investigated validity by quantifying correlations between measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
180
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(244 citation statements)
references
References 56 publications
20
180
1
2
Order By: Relevance
“…This is in line with the overall lower performance in Experiment 1 compared to Experiment 2 but is in contrast to the overall larger pupil size (relative to baseline) and larger effect of speech clarity in Experiment 2 compared to Experiment 1. The contrasting effects observed in the current study are consistent with the observation that different measures of listening effort and cognitive load are not or only minimally correlated (Miles et al, 2017;Alhanbali et al, 2019).…”
Section: Microsaccades Are Not Influenced By Semantic Ambiguity and Ssupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with the overall lower performance in Experiment 1 compared to Experiment 2 but is in contrast to the overall larger pupil size (relative to baseline) and larger effect of speech clarity in Experiment 2 compared to Experiment 1. The contrasting effects observed in the current study are consistent with the observation that different measures of listening effort and cognitive load are not or only minimally correlated (Miles et al, 2017;Alhanbali et al, 2019).…”
Section: Microsaccades Are Not Influenced By Semantic Ambiguity and Ssupporting
confidence: 90%
“…Although pupillometry recordings are increasingly used as a measure of listening effort (Winn et al, 2018;Zekveld et al, 2018), our data complement other data indicating that pupillometric measures do not always correlate with task performance measures or other measures of listening effort, such as subjective ratings or oscillatory neural activity (Hicks and Tharpe, 2002;Zekveld et al, 2010;Mackersie and Cones, 2011;Winn et al, 2015;Miles et al, 2017;Strand et al, 2018;Alhanbali et al, 2019). Part of the inconsistency may be due to the fact that the term 'listening effort' is ambiguous (Herrmann and Johnsrude, 2019) because it may refer to a mental act -associated with the recruitment of resources (Pichora-Fuller et al, 2016;Peelle, 2018) -or to a subjective experience (Johnsrude and Rodd, 2016;Lemke and Besser, 2016;Herrmann and Johnsrude, 2019).…”
Section: Relation Between Behavioral Performance and Pupil Dilationsupporting
confidence: 74%
“…In sum, the consistent decrease in effort versus peak-shape indicate that different methods indeed tap into different aspects of listening effort (Lemke & Besser, 2016;Alhanbali et al, 2019).…”
Section: Different Measures Reflect Different Aspects Of Listening Efmentioning
confidence: 99%
“…Lastly, several studies have also shown that the pupil size and eye movements can be used as physiological indicators of processing load (Zekveld et al, 2010(Zekveld et al, , 2018Koelewijn et al, 2014;Wendt et al, 2014). In spite of this, the neural mechanisms underlying the changes in pupil size are complex, resulting in different outcomes compared to other effort measures (Zekveld et al, 2018;Alhanbali et al, 2019). In addition, pupillometry is affected by several factors such as age, ambient light, and requires expensive equipment as well as specialized training which makes it difficult to implement it in the clinic or research (Houben et al, 2013;Winn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation